Local ubiquitin-proteasome-mediated proteolysis and long-term synaptic plasticity - Hegde, Ashok N.; Haynes, Kathryn A.; Bach, Svitlana V.; Beckelman, Brenna C. (Frontiers in Molecular Neuroscience, 2014)
The ubiquitin-proteasome pathway (UPP) of protein degradation has many roles in synaptic plasticity that underlies memory. Work on both invertebrate and vertebrate model systems has shown that the UPP regulates numerous substrates critical for synaptic plasticity. Initial research took a global view of ubiquitin-protein degradation in neurons. Subsequently, the idea of local protein degradation was proposed a decade ago. In this review, we focus on the functions of the UPP in long-term synaptic plasticity and discuss the accumulated evidence in support of the idea that the components of the UPP often have disparate local roles in different neuronal compartments rather than a single cell-wide function.